2010
DOI: 10.1128/aac.00474-10
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravenous Peramivir for Treatment of Seasonal Influenza Virus Infection

Abstract: Peramivir, a sialic acid analogue, is a selective inhibitor of neuraminidases produced by influenza A and B viruses. We evaluated the efficacy and safety of a single intravenous dose of peramivir in outpatients with uncomplicated seasonal influenza virus infection. A total of 300 previously healthy adult subjects aged 20 to 64 years with a positive influenza virus rapid antigen test were recruited within 48 h of the onset of influenza symptoms and randomized to three groups: single intravenous infusion of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
138
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 21 publications
3
138
1
Order By: Relevance
“…It was reported that peramivir increased survival rate of animals infected with lethal dose of influenza virus by the pharmaceutical company of peramivir, and its in vitro activity has been demonstrated to be comparable to or better than that of oseltamivir carboxylate and zanamivir [17,28]. Peramivir has been approved in Japan for the treatment of general seasonal influenza in adults, as a single dose of 300 mg intravenously [18,21]. A single dose or multiple daily doses of 600 mg of peramivir are administered intravenously depending on the condition of the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that peramivir increased survival rate of animals infected with lethal dose of influenza virus by the pharmaceutical company of peramivir, and its in vitro activity has been demonstrated to be comparable to or better than that of oseltamivir carboxylate and zanamivir [17,28]. Peramivir has been approved in Japan for the treatment of general seasonal influenza in adults, as a single dose of 300 mg intravenously [18,21]. A single dose or multiple daily doses of 600 mg of peramivir are administered intravenously depending on the condition of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Peramivir is a selective inhibitor of influenza neuraminidase that is effective when administrated intramuscularly and intravenously for the treatment of influenza virus infection in mouse models [17][18][19][20]23]. To analyze the effects of peramivir on influenza A (H1N1pdm) virus myocarditis, we investigated survival rates, cardiac function, histological findings and cytokine induction in murine influenza A (H1N1pdm) virus -induced myocarditis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, laninamivir is another long-acting NA inhibitor including oseltamivir-resistant viruses in adults [24,25]. Recently, peramivir has been approved in Japan for use in over 1 month of age [11].…”
Section: Introductionmentioning
confidence: 99%
“…This virus infects poultries and mammals. The common symptoms of this disease include headache, aches or pains in muscles or joints, feverishness, fatigue, cough, sore throat, and nasal congestion (see [9]). Children also may develop croup or bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%